Predictable quantum efficient detector based on n-type silicon photodiodes. (4th October 2017) - Dönsberg, Timo; Manoocheri, Farshid; Sildoja, Meelis; Juntunen, Mikko; Savin, Hele; Tuovinen, Esa; Ronkainen, Hannu; Prunnila, Mika; Merimaa, Mikko; Tang, Chi Kwong; Gran, Jarle; Müller, Ingmar; et al.
Abstract: The predictable quantum efficient detector (PQED) consists of two custom-made induced junction photodiodes that are mounted in a wedged trap configuration for the reduction of reflectance losses. Until now, all manufactured PQED photodiodes have been based on a structure where a SiO2 layer is thermally grown on top of p -type silicon substrate. In this paper, we present the design, manufacturing, modelling and characterization of a new type of PQED, where the photodiodes have an Al2 O3 layer on top of n -type silicon substrate. Atomic layer deposition is used to deposit the layer to the desired thickness. Two sets of photodiodes with varying oxide thicknesses and substrate doping concentrations were fabricated. In order to predict recombination losses of charge carriers, a 3D model of the photodiode was built into Cogenda Genius semiconductor simulation software. It is important to note that a novel experimental method was developed to obtain values for the 3D model parameters. This makes the prediction of the PQED responsivity a completely autonomous process. Detectors were characterized for temperature dependence of dark current, spatial uniformity of responsivity, reflectance, linearity and absolute responsivity at the wavelengths of 488 nm and 532 nm. For both sets of photodiodes, the modelled and measured responsivities were generally in agreement within the measurement and modelling uncertainties of around 100 parts per million (ppm). There is, however, an indication that the modelled internal quantum deficiency may be underestimated by a similar amount. Moreover, the responsivities of the detectors were spatially uniform within 30 ppm peak-to-peak variation. The results obtained in this research indicate that the n -type induced junction photodiode is a very promising alternative to the existing p -type detectors, and thus give additional credibility to the concept of modelled quantum detector serving as a primary standard. Furthermore, the manufacturing of PQEDs is no longer dependent on the availability of a certain type of very lightly doped p -type silicon wafers.